Discrete Signals with Special Correlation Properties - Kuznetsov, A.; Kovalchuk, D.; Kuznetsova, K.; Pastukhov, M.; Smirnov, O.; Prokopovych-Tkachenko, D. (CEUR-WS, 2019)
The methods of synthesis of discrete signals are analyzed with the special cross-correlation properties: m- sequences, signals of Legendre, Barker, Paley-Plotkin, Gold, small and large set of Kasami. Comparative researches of properties of the formed discrete signals are conducted. Separate direction develops in development of methods of forming of discrete signals, that is based on the use of algebraic and structural properties of circular shifts of group codes. It is shown that offered approach allows forming the great numbers of discrete sequences, ensemble and cross-correlation properties of that are set by the properties of the corresponding group controlled from distance, structural and cyclic.
Keywords: Discrete signals; cross-correlation and ensemble properties; group codes; circular shifts